2021
DOI: 10.1108/lodj-06-2020-0260
|View full text |Cite
|
Sign up to set email alerts
|

Silence and proactivity in managing supervisor ostracism: implications for creativity

Abstract: PurposeAnchored in a social control theory framework, this study aims to investigate the mediating effect of defensive silence in the relationship between employees' perception of supervisor ostracism and their creative performance, as well as the buffering role of proactivity in this process.Design/methodology/approachThe hypotheses were tested using three-wave survey data collected from employees in North American organizations.FindingsThe authors found that an important reason for supervisor ostracism adver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 87 publications
0
15
0
2
Order By: Relevance
“…Several articles analysed LMX as mediators of abusive supervision, close monitoring, authoritarian leadership and dark triad personality. Most of these studies concluded that social relationship mechanisms mediate the negative effects of various forms of ‘dark leadership’, such as abusive supervision and authoritarian leadership on creativity and innovation (Arshad et al., 2021; Chen & Appienti, 2020; Echebiri & Amundsen, 2020; Fodor et al., 2021; Gu et al., 2018; He et al., 2021; Jahanzeb et al., 2021; Meng et al., 2017; Son et al., 2017; Syed et al., 2021; Tan et al., 2021). It has been shown that ‘dark leaders’ burden their subordinates with their behaviour, thereby limiting their cooperation.…”
Section: Resultsmentioning
confidence: 99%
“…Several articles analysed LMX as mediators of abusive supervision, close monitoring, authoritarian leadership and dark triad personality. Most of these studies concluded that social relationship mechanisms mediate the negative effects of various forms of ‘dark leadership’, such as abusive supervision and authoritarian leadership on creativity and innovation (Arshad et al., 2021; Chen & Appienti, 2020; Echebiri & Amundsen, 2020; Fodor et al., 2021; Gu et al., 2018; He et al., 2021; Jahanzeb et al., 2021; Meng et al., 2017; Son et al., 2017; Syed et al., 2021; Tan et al., 2021). It has been shown that ‘dark leaders’ burden their subordinates with their behaviour, thereby limiting their cooperation.…”
Section: Resultsmentioning
confidence: 99%
“…According to Lee et al (2022) and Maqbool et al (2019) employee silence also negatively affects employee innovation behavior. Employees’ Defensive Silence has a negative relationship with creativity ( Jahanzeb et al, 2021 ). Employees’ silence-based behavior may deprive them of any chance to offer original contributions, which limits their creativity in work environments ( Wynen et al, 2020 ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Nurses’ silence can mediate the link between toxic leadership and organizational performance ( Farghaly Abdelaliem and Abou Zeid, 2023 ). Employees’ sense of supervisor rejection and their creativity are mediated by defensive silence ( Jahanzeb et al, 2021 ). The findings of Broeng’s research suggest that tacit silence mediates some of the mechanisms by which organizational justice influences emotional exhaustion and withdrawal ( Broeng, 2018 ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Employees' proactive behavior at workplace is useful for themselves as well as organizations (Parker et al, 2019). Employees' proactivity is likely to increase job capability (Zhang and Edgar, 2021), reduce employees' perception of supervisor ostracism (Jahanzeb et al, 2021), enrich work-family relationship (Cui and Zhang, 2021), increase employee initiatives (Gorgijevski et al, 2019), enhance job crafting (Jiang et al, 2021), build meaningfulness at work (Wong et al, 2020), develop career adaptability (Green et al, 2020), augment firm profitability (Brulhart et al, 2019), bring organization change and development (Presbitero and Teng-Calleja, 2017) and develop organizational resilience (Cruickshank, 2020). According to the proactivity literature, it can be concluded that employees' proactivity not only helps to achieve an individual's goals but also ensures the accomplishment of organizational goals.…”
Section: Introductionmentioning
confidence: 99%
“…, 2019). Employees' proactivity is likely to increase job capability (Zhang and Edgar, 2021), reduce employees' perception of supervisor ostracism (Jahanzeb et al. , 2021), enrich work–family relationship (Cui and Zhang, 2021), increase employee initiatives (Gorgijevski et al.…”
Section: Introductionmentioning
confidence: 99%